Identification and Classification for the Lactobacillus casei Group - Huang, Chien-Hsun; Li, Shiao-Wen; Huang, Lina; Watanabe, Koichi (Frontiers in Microbiology, 2018)
Lactobacillus casei, Lactobacillus paracasei, and Lactobacillus rhamnosus are phenotypically and genotypically closely related, and together comprise the L. casei group. Although the strains of this group are commercially valuable as probiotics, the taxonomic status and nomenclature of the L. casei group have long been contentious because of the difficulties in identifying these three species by using the most frequently used genotypic methodology of 16S rRNA gene sequencing. Long used as the gold standard for species classification, DNA‒DNA hybridization is laborious, requires expert skills, and is difficult to use routinely in laboratories. Currently, genome-based comparisons, including average nucleotide identity (ANI) and digital DNA‒DNA hybridization (dDDH), are commonly applied to bacterial taxonomy as alternatives to the gold standard method for the demarcating phylogenetic relationships. To establish quick and accurate methods for identifying strains in the L. casei group at the species and subspecies levels, we developed species- and subspecies-specific identification methods based on housekeeping gene sequences and whole-cell matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) spectral pattern analysis. By phylogenetic analysis based on concatenated housekeeping gene sequences (dnaJ, dnaK, mutL, pheS, and yycH), 53 strains were separated into four clusters corresponding to the four species: L. casei, L. paracasei and L. rhamnosus, and Lactobacillus chiayiensis sp. nov. A multiplex minisequencing assay using single nucleotide polymorphism (SNP)-specific primers based on the dnaK gene sequences and species-specific primers based on the mutL gene sequences provided high resolution that enabled the strains at the species level to be identified as L. casei, L. paracasei, and L. rhamnosus. By MALDI-TOF MS analysis coupled with an internal database and ClinProTools software, species- and subspecies-level L. casei group strains were identified based on reliable scores and species- and subspecies-specific MS peaks. The L. paracasei strains were distinguished clearly at the subspecies level based on subspecies-specific MS peaks. This article describes the rapid and accurate methods used for identification and classification of strains in the L. casei group based on housekeeping gene sequences and MALDI-TOF MS analysis as well as the novel speciation of this group including L. chiayiensis sp. nov. and ‘Lactobacillus zeae’ by genome-based methods.